Implications of the non-specific effect induced by Bacillus Calmette-Guerin (BCG) vaccine on vaccine recommendations - Ekaterini Goudouris; Carolina Sanchez Aranda; Dirceu Solé (Jornal de Pediatria, 2023)
Objectives: Since the beginning of its use for the prevention of tuberculosis (TB) in 1921, other uses of BCG (Bacillus Calmette-Guérin) have been proposed, particularly in the treatment of malignant solid tumors, multiple sclerosis, and other autoimmune diseases. Its beneficial impact on other infections, by nontuberculous mycobacteria, and by viruses, has been more often studied in recent years, especially after the introduction of the concept of trained immunity. The present study's objective was to review the possible indications of BCG and the immunological rationale for these indications. Data source: Non-systematic review carried out in the PubMed, SciELO and Google Scholar databases, using the following search terms: “BCG” and “history”, “efficacy”, “use”, “cancer”, “trained immunity”, “other infections”, “autoimmune diseases”. Data synthesis: There is epidemiological evidence that BCG can reduce overall child morbidity/mortality beyond what would be expected from TB control. BCG is able to promote cross-immunity with nontuberculous mycobacteria and other bacteria. BCG promotes in vitro changes that increase innate immune response to other infections, mainly viral ones, through mechanisms known as trained immunity. Effects on cancer, except bladder cancer, and on autoimmune and allergic diseases are debatable. Conclusions: Despite evidence obtained from in vitro studies, and some epidemiological and clinical evidence, more robust evidence of in vivo efficacy is still needed to justify the use of BCG in clinical practice, in addition to what is recommended by the National Immunization Program for TB prevention and bladder cancer treatment.